14q12q13.3 Deletion Diagnosed Using Chromosomal Microarray Analysis in an Infant Showing Seizures, Hypoplasia of the Corpus Callosum, and Developmental Delay - Jae Hyuk Kwon; Young Hwa Song; Jung Min Yoon; Eun Jung Cheon; Kyung Ok Ko; Jae Woo Lim; Hyon J. Kim (Korean Society of Neonatology, 2020)
14q12q13.3 Deletion is a rare microdeletion syndrome associated with neurodevelopmental delay, failure to thrive, seizures, and abnormal brain development. Symptoms vary depending on the sites of gene deletion, and establishing the diagnosis is often difficult, as the condition cannot be detected with routine chromosome analysis. In this report, we present a patient with intrauterine growth retardation, microcephaly, muscle weakness, seizures, and hypoplasia of the corpus callosum who underwent diagnostic tests, including karyotyping in the neonatal period without leading to a specific diagnosis. The patient was confirmed with a serious developmental disorder, and a chromosomal microarray analysis was performed at 8 months of age, revealing a 14q12q13.3 deletion. In this case, the condition was diagnosed in early infancy, in contrast to previously reported cases, and the patient had diverse and severe symptoms. Establishing the diagnosis of 14q12q13.3 deletion syndrome allows better management of patient care and genetic counseling for the parents.